Educating tomorrow : learning for the post-pandemic world - Brown, C. H.; Luzmore, Ruth (Emerald Publishing Limited, 2021)
The post-pandemic world provides all of us with the opportunity to think differently about what we want for society. In Educating Tomorrow, Chris Brown and Ruth Luzmore explore what a post-Covid 'blank slate' education system could look like. Taking you on a journey which considers the past and present to inform their prediction of the obstacles and opportunities posed by a post-pandemic future, the authors present a new vision for the future of education which might not have been possible without the eruption of Covid-19. Offering up a range of proposals for how education can begin to emerge anew, and ultimately reach an improved destination, Brown and Luzmore showcase how even in the midst of unprecedented global challenges, it might be possible for us to revolutionise education systems for the better.
Includes index.
Keywords: Educational change.; Education -- General.; Education.; elektronické knihy; electronic books